Age-Related Differences in Fixation Gaze Length While Reading the News with Negative Text Elements - Ivaskevych, Daryna; Popov, Anton; Rizun, Volodymyr; Havrylets, Yurii; Petrenko-Lysak, Alla; Yachnik, Yuliia; Tukaiev, Sergii (Lesya Ukrainka Eastern European National University, 2023)
The worldwide COVID-19 pandemic has led to the development of stress disorders and increased societal anxiety. The mass media is one of the most decisive factors leading to the development of anxiety and stress in society during a pandemic. However, the mechanisms of mass media's stressogenic effects remain unclear. This study aimed to evaluate age-specific characteristics of gaze behavior related to the perception of anxiety-provoking information. One hundred eighty-nine volunteers took part in the study (164 participants aged between 17 and 22 years old (students, control group), 25 people aged between 59 and 71 (experimental group)). We surveyed participants to determine their level of stress, depression, and anxiety and analyzed eye-tracking data during text perception by using the web eye-tracking technology EyePass. Results showed significant age-related differences in gaze behavior while reading texts with negative elements. Aged adults had shorter median fixation duration. There was no difference between groups in the number of fixations. We can assume that except age factor, other variables might have contributed to our result, namely the occupation of participants, professors at the Scientific and Educational Institute of Journalism, with developed professional skills (reading pattern, method of information perception) but from another side higher vulnerability to adverse COVID-19 outcomes compared to younger adults.
Keywords: mass media; COVID-19 pandemic; gaze behavior; fixation; eye tracking